1977
DOI: 10.2307/3428480
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arsenic Cell Metabolism and Cell Proliferation: Cytogenetic and Biochemical Studies

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) andBrogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…(cohort continuously exposed to arsenic) 30 For individuals whose exposure had stopped, i.e., those who terminated their employment, the multistage theory predicts that their excess cancer risk after cessation of employment will be an increasing function of exposure duration and concentration, and will also be independent of age started exposure (if only the first stage is affected) or follow-up time since exposure stopped (if only the penultimate stage is affected). The indirect adjustment method was applied to the data in Table 4 to produce excess lung cancer mortality rates for each of these four factors adjusted for the possible confounding effects of the other three factors.…”
Section: Resultsmentioning
confidence: 99%
“…(cohort continuously exposed to arsenic) 30 For individuals whose exposure had stopped, i.e., those who terminated their employment, the multistage theory predicts that their excess cancer risk after cessation of employment will be an increasing function of exposure duration and concentration, and will also be independent of age started exposure (if only the first stage is affected) or follow-up time since exposure stopped (if only the penultimate stage is affected). The indirect adjustment method was applied to the data in Table 4 to produce excess lung cancer mortality rates for each of these four factors adjusted for the possible confounding effects of the other three factors.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of radioactively labelled nucleotides in dermal cells and lymphocytes was reduced by sodium arsenate (84,85). Incorporation of radioactively labelled nucleotides in dermal cells and lymphocytes was reduced by sodium arsenate (84,85).…”
Section: Metabolism and Mechanism Of Effectsmentioning
confidence: 99%
“…An increased frequency of chromosomal aberrations has been observed among workers exposed to inorganic arsenic compounds, as well as in patients who had taken drugs containing arsenic (85,89). Chromosomal aberrations have also been produced 96 Environmental Health Perspectives in vitro by inorganic arsenic salts (90,91).…”
Section: Metabolism and Mechanism Of Effectsmentioning
confidence: 99%
“…PETRES et al (1970PETRES et al ( , 1977 found increased frequencies of chromosomal aberrations in psoriatic patients treated therapeutically with arsenic and in wine growers exposed to arsenic-containing pesticides. PETRES et al (1970PETRES et al ( , 1977 found increased frequencies of chromosomal aberrations in psoriatic patients treated therapeutically with arsenic and in wine growers exposed to arsenic-containing pesticides.…”
mentioning
confidence: 99%